Pattern of antibiotic and heavy-metal ion resistance in recent hospital isolates of Staphylococcus aureus. - Millar, M. R. (Cambridge University Press, 1987)
Two hundred and one strains of Staphylococcus aureus isolated from in-patients and out-patients were examined for sensitivity to antibiotics, heavy-metal ions and ethidium bromide and for phage-typing pattern. Heavy-metal ion resistance was less frequent than reported in previous studies and was as frequent in penicillinase non-producing as producing strains. 'Methicillin-resistant' strains were resistance to ethidium bromide and mercury. Resistance to heavy-metal ions, including cadmium, may be becoming less common amongst clinical isolates of S. aureus.